2024
DOI: 10.1002/cphc.202400147
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Lipopolysaccharides on the Electrostatic Properties of Gram‐Negative General Porins from Enterobacteriaceae

Matteo Ceccarelli,
Stefan Milenkovic,
Igor V. Bodrenko

Abstract: We investigated, by using all‐atom molecular dynamics simulations, the effect of the asymmetric outer membrane layer of Gram‐negative bacteria, composed in the outer leaflet by polar/charged lipopolysaccharides (LPS), on the electrostatic properties of general porins from the Enterobacteriaceae family. These porins constitute the main path for the facilitated diffusion of polar antibiotics to cross the outer membrane. As model system we selected OmpK36 from Klebsiella pneumoniae, the ortholog of OmpC from Esch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 67 publications
0
2
0
Order By: Relevance
“…coli permeability through general porins . While other size-related descriptors have already been included so far, whose importance emerged in the previous sections of this manuscript, the dipole moment is of special interest because of its direct role in the interaction with the electrostatics of the porin lumen. ,, These bacterial protein channels have their characteristic internal electric field, with the molecular dipole’s interaction contributing to the transport process’s total free energy. This, in turn, will lead to a quantitative effect on both permeability and accumulation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…coli permeability through general porins . While other size-related descriptors have already been included so far, whose importance emerged in the previous sections of this manuscript, the dipole moment is of special interest because of its direct role in the interaction with the electrostatics of the porin lumen. ,, These bacterial protein channels have their characteristic internal electric field, with the molecular dipole’s interaction contributing to the transport process’s total free energy. This, in turn, will lead to a quantitative effect on both permeability and accumulation.…”
Section: Resultsmentioning
confidence: 99%
“…Permeability is a nonlocal property and relies on a statistical description, depending on an integral over a free energy surface . Studies on permeability through OMPs in Escherichia coli by Ceccarelli et al emphasized the significance of interactions between the translocating molecules and the transport medium. These interactions offer insights to identify highly permeating molecules. Further, it was shown that the sole use of mean values for physicochemical molecular descriptors is not enough to catch their statistical variability.…”
Section: Introductionmentioning
confidence: 99%